Meningkatkan Kemampuan Pemahaman Dan Koneksi Matematis Peserta Didik Melalui Problem Based Learning - Setiawati, Keuis Letti (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
The purpose of this research is to find out the students’ mathematics connection and comprehension ability in which problem based learning is used in learning process to increase the students’ mathematic connection comprehension ability since it is better than conventional method according to the learning class and Early Mathematic Ability(EMA). Besides, the experiment with group design control pretest-posttest and Embedded Conkuren strategy are used as a research method; it is qualitative method utilized into quantitative method. The population of this research is all of the eleventh science students of SMAN 1 Tasikmalaya 2014. Then, it will be selected only two classes which become a sample in this researchaccomplished by using random sampling. Research instrument consists of questions of the students’ mathematic connection and comprehension ability, and the observation sheet of the students and the teacher’s activity. In addition, T test and two ways ANOVA test are used as a quantitative analysis data and it will be continued by using Scheffe test. Analizing qualitatively is accomplished to the students and the teacher’s activity. The acquired conclusion from this research is 1) using problem based learning is better than conventional method to improve the students’ mathematics comprehension ability generally and Early Mathematic Ability(EMA), 2) using problem based learning is better than conventional method to improve the students’ mathematics connection and Early Mathematic Ability(EMA), 3) there is correlation between the students’ mathematics connection and comprehension ability, 4) the students and the teacher’s activity is improve in every meeting in accomplishing mathematics learning by using problem based learning method.